Microbial community structure and functional characteristics across the mucosal surfaces of olive flounder (Paralichthys olivaceus) - Jihyun Yu; Jihyun Yu; Min Joo Kang; Mi-Jeong Park; Gyeong Hak Han; Gyeong Hak Han; Yun Jae Kim; Yun Jae Kim; Choong Hwan Noh; Kae Kyoung Kwon; Kae Kyoung Kwon (Frontiers in Microbiology)
The mucosal surfaces of aquatic animals serve as a functional barrier between the host and the aquatic environment, hosting diverse microbial communities that play pivotal roles in host health. In this study, amplicon libraries of the 16S rRNA gene were constructed to investigate the compositional differences between the microbial communities presented in four mucosal surfaces (gills, skin, gut, and ovary) of spawning female olive flounder. To elucidate the unique roles of commensal microbes in external and internal organs, we used PICRUSt2 and ALDEx2, respectively, to predict metabolic functions and identify differential abundances of microbes. Microbial richness was significantly higher in the gills and skin, which are directly exposed to seawater, compared to the intestine and ovary, which are relatively oxygen-poor internal environments. Compositional analysis revealed that the gill mucus was dominated by unclassified Comamonadaceae, a member of the Burkholderiales. While skin mucus shared constituents with gills and intestines, it also harbored unique taxa, including obligate intracellular parasites such as Rickettsiales and Chlamydiales. In contrast, the intestinal and ovarian mucus were dominated by the family Vibrionaceae of Gammaproteobacteria. Functional predictions highlighted the distinct ecological roles of the mucosal microbiota. The gills and skin were enriched in functions related to denitrification, sulfur oxidation, B-group vitamin synthesis, and photosynthesis, reflecting their adaptation to external environmental exposure. Conversely, the intestine was characterized by functions such as beta-lactamase and phenicol resistance, glycosidases, LPS synthesis, and vitamin K2 production. These findings support the idea that while the microbiota of internal organs primarily supports digestive and immunological processes, the symbionts of external organs may play crucial roles in neutralizing toxic compounds from aquaculture practices, such as reduced nitrogen and sulfur compounds, and maintaining the integrity of the mucosal barrier.